The Journey of Gender analysis in Livestock and Fish and Livestock CRP - Galiè, Alessandra (2021)
Presentation by Alessandra Galiè, Livestock CRP gender leader, on the evolution of the gender role and approach within the livestock-based CRPs. This presentation was delivered as part of the golden eggs session of the final celebration and closing meeting of the CGIAR Research Program on Livestock in Oct 2021.